The path to host extinction can lead to loss of generalist parasites. (4th March 2015) - Farrell, Maxwell J.; Stephens, Patrick R.; Berrang‐Ford, Lea; Gittleman, John L.; Davies, T. Jonathan; Fenton, Andrew
Summary Host extinction can alter disease transmission dynamics, influence parasite extinction and ultimately change the nature of host–parasite systems. While theory predicts that single‐host parasites are among the parasite species most susceptible to extinction following declines in their hosts, documented parasite extinctions are rare. Using a comparative approach, we investigate how the richness of single‐host and multi‐host parasites is influenced by extinction risk among ungulate and carnivore hosts. Host–parasite associations for free‐living carnivores (order Carnivora) and terrestrial ungulates (orders Perissodactyla + Cetartiodactyla minus cetaceans) were merged with host trait data and IUCN Red List status to explore the distribution of single‐host and multi‐host parasites among threatened and non‐threatened hosts. We find that threatened ungulates harbour a higher proportion of single‐host parasites compared to non‐threatened ungulates, which is explained by decreases in the richness of multi‐host parasites. However, among carnivores threat status is not a significant predictor of the proportion of single‐host parasites, or the richness of single‐host or multi‐host parasites. The loss of multi‐host parasites from threatened ungulates may be explained by decreased cross‐species contact as hosts decline and habitats become fragmented. Among carnivores, threat status may not be important in predicting patterns of parasite specificity because host decline results in equal losses of both single‐host parasites and multi‐host parasites through reduction in average population density and frequency of cross‐species contact. Our results contrast with current models of parasite coextinction and highlight the need for updated theories that are applicable across host groups and account for both inter‐ and intraspecific contact.